2007
DOI: 10.1532/ijh97.06203
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for Efficient Production of Multipotential Hematopoietic Progenitors from Human Embryonic Stem Cells

Abstract: We propose a novel method for the efficient production of hematopoietic progenitors from human embryonic stem cells (hESC) via coculture with murine fetal liver-derived stromal cells, in which embryonic hematopoiesis dramatically expands at midgestation. We generated various hematopoietic progenitors in coculture, and this hematopoietic activity was concentrated in cobblestone-like cells derived from differentiated hESC. The cobblestone-like cells mostly expressed CD34 and retained an endothelial cell potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…1C). Genes for initial development of endothelial/ hematopoietic cells were expressed early in the coculture, as reported in our previous work (8). The expression of ␤-globin could be detected by day 10, consistent with the immunostaining results.…”
Section: Generation Of Erythroid Cells From Hescs By Coculture With Msupporting
confidence: 90%
See 4 more Smart Citations
“…1C). Genes for initial development of endothelial/ hematopoietic cells were expressed early in the coculture, as reported in our previous work (8). The expression of ␤-globin could be detected by day 10, consistent with the immunostaining results.…”
Section: Generation Of Erythroid Cells From Hescs By Coculture With Msupporting
confidence: 90%
“…In a previous study (8), we found that the production of erythroid progenitors from hESCs was greatly enhanced by coculture with mFLSCs. This experimental paradigm provides the opportunity to conduct large-scale investigations of hESC-derived erythropoiesis.…”
Section: Generation Of Erythroid Cells From Hescs By Coculture With Mmentioning
confidence: 80%
See 3 more Smart Citations